Systems and Virtualization Management. Standards and the Cloud Third International DMTF Academic Alliance Workshop, SVM 2009, Wuhan, China, September 22-23, 2009. Revised Selected Papers - Boursas, Latifa; Carlson, Mark.; Jin, Hai.; Sibilla, Michelle; Wold, Kes.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This volume constitutes the refereed proceedings of the Third International DMTF Academic Alliance Workshop, SVM 2009, held in Wuhan, China, in September 2009.
Power Management Challenges in Virtualization Environments -- Chinese Wall Isolation Mechanism and Its Implementation on VMM -- Visualization-Based Study on Information Specification Languages for Network Management Using Formal Concept Analysis -- CORSET: Service-Oriented Resource Management System in Linux -- A Technology Explore for the Content-Based Web Query Service on MODIS Level 1B Products -- CFCC: A Covert Flows Confinement Mechanism for Virtual Machine Coalitions -- Automatic Cache Update Control for Scalable Resource Information Service with WS-Management -- Fast Booting Many Similar Virtual Machines -- On I/O Virtualization Management -- Availability Management in a Virtualized World -- Enhancing Trust in SOA Based Collaborative Environments.
Keywords: Computer science; Computer Communication Networks; Software engineering; Database management; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Information Systems Applications (incl.Internet).; Computer Communication Networks; Information Storage and Retrieval; Software Engineering; Artificial Intelligence (incl. Robotics).; Database Management